Legal Culture of State Officials Regarding Violations of the Code of Ethics in the East Java Regional Police - Hendra Wirawan; Toetik Koesbardiati; Sutinah Sutinah (Indonesian Journal of Administrative Law and Local Government, 2024)
The police code of ethics is a set of behavioral rules that regulate the maintenance of the integrity and professionalism of the police institution. In practice, there are violations of the code of ethics by police officers, which can tarnish the professionalism of the police institution. This research focuses on ethical code violations that occur at the East Java Regional Police. This research is an empirical legal study with primary data in the form of interviews and secondary data including journal articles, books, and legislation. The research results show that the command law culture, which has been internalized by every member of the National Police in East Java Regional Police, is such that if higher-ranking police officers do not adhere to the code of ethics, this behavior is also followed by lower-ranking police officers. The influential factor related to code of ethics violations in East Java Regional Police is the leadership style of superiors, which is one of the reasons for the continued code of ethics violations by lower-ranking police officers due to their disagreement with the decisions made by their superiors. The recommendation of this research is that there needs to be exemplary behavior from superiors to ensure that members can adhere to the police code of ethics, thereby creating a culture of law that complies with the code of ethics for police officers. Additionally, the cultivation of a responsive and accommodative leadership style is necessary so that superiors can become wiser in giving directions or orders to subordinates.